An Unprecedented Tandem Annulation of ω-Azido-1-alkynes with Diaryliodonium Salts: A Facile Synthesis of Polycyclic Quinolines - Chen, Junjie; Chen, Chao; Chen, Jing; Gao, Hongpeng; Qu, Hongmei (Synlett, 2014)
Polysubstituted quinolines are synthesized through an unprecedented cascade annulation of ω-azido-1-alkynes with diaryliodonium salts, which serve as C2-building blocks. The reaction proceeds smoothly and is catalyzed by Cu(I) catalysts to give various quinolines in good isolated yields with simple operation under mild conditions.
Keywords: quinolines; azides; alkynes; copper catalyst; tandem annulation